Indonesian EFL Teachers’ Roles and Challenges in a Virtual Teaching Environment - Aulia, Mutiara Putri; Suherdi, Didi; Muslim, Ahmad Bukhori (International Journal of Education, 2021)
Abrupt change into virtual classroom teaching due to the COVID-19 pandemic has forced teachers to switch to teaching roles different from the conventional classroom. Facing this unprecedented condition, many teachers have experienced confusion in switching to appropriate roles in order to engage their students in the learning process. This study explores Indonesian EFL teachers’ roles during online teaching activities and possible challenges in having teaching practices amid pandemics. Data for this qualitative study were generated from virtual classroom observations, field notes and semi-structured interviews of two high school teachers. Borrowing the lens of Alvarez et al. (2009) and Harmer (2007) for analysis, the study identified different design/planning, social and cognitive roles of Indonesian EFL teachers such as controller, prompter and resource. While exploring more relevant roles, teachers also faced some constraints in running online teaching practices like poor internet connection and the lack of face-to-face interaction during the process of teaching and learning practices. In conclusion, Indonesian EFL teachers can still perform designer/planning, social and cognitive roles. However, their specific roles are limited to controller, prompter and resource only due to the obstacles involved in the virtual classrooms.